Effects of Flexible Transfemoral Prostheses on Dynamic Balance in Unilateral Amputees: A Quasi-Experimental Within-Subject Study - Rachmat, Nur; Kuncoro, Bambang (Journal of Applied Nursing and Health, 2026)
Background: Dynamic balance impairment is a major functional challenge in individuals with transfemoral amputation and is closely associated with mobility limitations and increased fall risk. Flexible transfemoral prostheses are widely prescribed to improve ambulation. However, limited biomechanical evidence exists examining how flexible transfemoral prostheses influence dynamic balance performance using standardized functional clinical assessments. This study aimed to examine the effect of flexible transfemoral prosthesis use on dynamic balance in unilateral transfemoral amputees. Methods: This quasi-experimental within-subject study followed the TREND reporting guideline. Thirty unilateral transfemoral amputees were recruited using purposive sampling from the Department of Prosthetics and Orthotics at Poltekkes Kemenkes Surakarta, Indonesia. Inclusion criteria were medical stability and ability to perform multidirectional stepping; exclusion criteria included bilateral amputation and neurological disorders. The independent variable was ambulation condition (axillary crutch ambulation versus flexible transfemoral prosthesis use), and the dependent variable was FSST completion time. Dynamic balance was assessed using the Four Square Step Test (FSST). Analyses were conducted using paired t-tests with 95% confidence intervals. Results: Participants were predominantly male (76.7%) with a mean age of 33.6 ± 9.4 years and a mean post-amputation duration of 4.2 ± 2.1 years. FSST completion time significantly decreased during flexible transfemoral prosthesis use compared with axillary crutch ambulation (mean difference = 8.97 seconds; 95% CI, 7.72–10.22; p < 0.001), demonstrating a very large effect size (Cohen’s d = 2.68). Conclusion: Flexible transfemoral prosthesis use significantly enhances dynamic balance in unilateral transfemoral amputees. Flexible transfemoral prostheses should be considered an essential component of function-oriented rehabilitation strategies to optimize postural control and safe mobility. Future longitudinal and instrumented biomechanical studies are warranted to further elucidate underlying adaptation mechanisms.